Tebuconazole induced cardiotoxicity in male adult rat. (March 2020) - Ben Othmène, Yosra; Hamdi, Hiba; Annabi, Emna; Amara, Ines; Ben Salem, Intidhar; Neffati, Fadwa; Najjar, Mohamed Fadhel; Abid-Essefi, Salwa
Abstract: Tebuconazole is an effective systemic fungicide that belongs to the triazoles family. It has been widely used in both agricultural and medical sectors for the control of fungal diseases. Although TEB poses serious threats to mammals health, studies regarding its cardiotoxicity are very limited. Thus, we aimed to evaluate the effects of TEB on some biochemical parameters, the induction of apoptosis and DNA damage in the heart tissue. Male Wistar rats were treated with TEB at varied oral doses for 28 consecutive days. This study demonstrates that TEB decreased cardiac acetylcholinesterase, increased serum marker enzymes such as creatinine phosphokinase (CPK) and lactate dehydrogenase (LDH), and altered the lipid profile by increasing serum levels of total cholesterol (T-CHOL), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) and reduced high-density lipoprotein cholesterol (HDL-C) levels. Furthermore, TEB increased levels of p53 and Bax/Bcl2 ratio, released the cytochrome c into the cytosol and activated caspase-9 and caspase-3. Besides, our results showed that TEB induced genotoxic effects. TEB induced DNA fragmentation and increased the frequency of micronucleated bone marrow cells. Moreover, TEB treatment developed fibrosis in the myocardium. Our results suggest that TEB exposure may affect myocardial cells normal functioning and triggers apoptosis. Graphical abstract: Image 1 Highlights: TEB induced biochemical changes in male Wistar rats. TEB triggered apoptosis in cardiac cells. TEB induced DNA fragmentation and micronuclei formation. TEB induced myocardial fibrosis.